2023
DOI: 10.3934/math.2023637
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis and design of cooperative control for linear delta operator system

Abstract: <abstract><p>This paper investigates the cooperative state feedback control problem for delta operator-based large-scale systems with independent subsystems. First, the state feedback controller is introduced to interconnect the adjacent subsystems into a closed-loop system. Second, the Lyapunov function in delta domain is constructed, and the linear matrix inequality method is used to design the cooperative state feedback stability controller for the whole large-scale interconnected system. Third,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Introducing current popular research directions such as stochastic control and adaptive control into the study of SLBRS would undoubtedly open up new possibilities. For more details, please refer to the latest literature [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Introducing current popular research directions such as stochastic control and adaptive control into the study of SLBRS would undoubtedly open up new possibilities. For more details, please refer to the latest literature [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the widespread applications of time delay in various technical domains such as engineering technology, mechanics, cybernetics and biomedicine, the research scope of TDS has gained prominence among researchers. Specifically, comprehensive research on TDS stability revealed a critical issue pertaining to control theory, which has been assessed in various monographs [1][2][3][4][5][6][7][8][9][10][11][12][13]. For example, in [14], Zhao and Zhu discussed a neutral stochastic highly nonlinear time-delay system with a nonlinear growth condition.…”
Section: Introductionmentioning
confidence: 99%
“…Model (1) can be viewed as an extension of the classic deterministic mathematical programming problem. It is closely related to the distributionally robust optimization model, as well as optimization problems with stochastic dominance constraints, which have received considerable attention over the past decade for their theoretical importance and extensive applications (for more details, please refer to references [1][2][3][4][5][6][7][8][9][10] and the references therein).…”
Section: Introductionmentioning
confidence: 99%